2002
DOI: 10.1042/cs1030311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the protein kinase Cβ inhibitor LY333531 on neural and vascular function in rats with streptozotocin-induced diabetes

Abstract: Elevated protein kinase C activity has been linked to the vascular and neural complications of diabetes. The aim of the present study was to examine the involvement of the beta-isoform of protein kinase C in abnormalities of neuronal function, neural tissue perfusion and endothelium-dependent vasodilation in diabetes, by treatment with the selective inhibitor LY333531 (10 mg.kg(-1).day(-1)). Diabetes was induced in rats by streptozotocin; the duration of diabetes was 8 weeks. Nerve conduction velocity was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Animal models of diabetic neuropathy demonstrate a reduction in nerve conduction velocity and blood flow [16] yet they do not show structural changes observed in human diabetic neuropathy and there is controversy as to whether the changes they do show are due to maturational delay induced by hyperglycaemia, or due to diabetes itself [17,18]. Experimental studies demonstrate progressive molecular alterations leading to nodal and paranodal degeneration with axo-glial dysjunction and axonal atrophy [19].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of diabetic neuropathy demonstrate a reduction in nerve conduction velocity and blood flow [16] yet they do not show structural changes observed in human diabetic neuropathy and there is controversy as to whether the changes they do show are due to maturational delay induced by hyperglycaemia, or due to diabetes itself [17,18]. Experimental studies demonstrate progressive molecular alterations leading to nodal and paranodal degeneration with axo-glial dysjunction and axonal atrophy [19].…”
Section: Introductionmentioning
confidence: 99%
“…These investigations show for the first time that this beneficial effect relates to its ability to reverse endothelium-dependent vasodilator responses and correct deficits in neural blood flow [15]. The observation that LY333531 can successfully reverse established abnormalities in these experiments gives considerable hope that a new treatment for diabetic microvascular complications is a realistic prospect in the not too distant future.…”
Section: New Hope For the Treatment Of Diabetic Complicationsmentioning
confidence: 75%
“…In this issue of Clinical Science, Cotter et al [15] show that LY333531 also reverses neuronal dysfunction in diabetic rats. These investigations show for the first time that this beneficial effect relates to its ability to reverse endothelium-dependent vasodilator responses and correct deficits in neural blood flow [15].…”
Section: New Hope For the Treatment Of Diabetic Complicationsmentioning
confidence: 99%
“…Ishii et al first showed that oral administration of highly selective PKC-β inhibitor ruboxistaurin mesylate (LY333531) inhibits the phosphorylation of PKC-β 2 and PKC-α in diabetic rats thereby decreasing the glomerular filtration, albumin excretion and retinal circulation in a dose-responsive manner [86]. Subsequent studies with ruboxistaurin proved that it delays the progression of diabetic retinopathy, nephropathy, and neuropathy in animal models [83,[87][88][89][90]. Ruboxistaurin has been successfully tested in clinical studies.…”
Section: Ruboxistaurinmentioning
confidence: 99%